If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16x + -15 = 17 Reorder the terms: -15 + -16x = 17 Solving -15 + -16x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -16x = 17 + 15 Combine like terms: -15 + 15 = 0 0 + -16x = 17 + 15 -16x = 17 + 15 Combine like terms: 17 + 15 = 32 -16x = 32 Divide each side by '-16'. x = -2 Simplifying x = -2
| 2(x+5)(x-5)=0 | | X-10=7x-82 | | 2p^2+12p+14=0 | | 4(5x+3)=3(7x-1) | | y+32=77 | | 47261/4 | | 25x=375 | | 3x-14=21 | | 0.04x+0.05(20-x)=0.95 | | 0.5d-0.2d-17=13 | | -6x(4x+1)+4= | | zsquared-14z=70 | | (2)(1.1)=3/x | | -3x(4x-3)=33 | | 28p^2-168p-196=0 | | 10+7x=82-x | | 2.2x+43.1=5.9-10.2x | | Lnq=19 | | 2x(7x^2-34x-5)=0 | | 8x=2x+54 | | -15x+54=-81 | | 2x^2-25x+25=0 | | -159+4x=-6x+111 | | -7r=35 | | -15-x=11-3x | | 4x^2+29c=-45 | | Z^2-3(z+2)=4 | | 21-5x=1x-9 | | 10k-3/-33 | | 15x-2= | | -100+6x=-2x+124 | | 5(2c+6)+1=25 |